Improving the Recovery of Hydrocarbons in a Well in the Gullfaks Field by Injecting Sequestrated CO2 - Cheage Chamgoué, André; Kombou, Colins Leprince; Tchouate Ngankap, Merline; Metsebo, Jules; Armstrong Akoteh, Ateh (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The Gullfaks field was discovered in 1978 in the Tampen area of the North Sea and it is one of the largest Norwegian oil fields located in Block 34/10 along the western flank of the Viking Graben in the northern North Sea. The Gullfaks field came on stream in 1986 and reached a peak of production in 2001. After some years, a decrease in production was noticed due to the decrease in pressure in the well. The goal of this paper is to improve the production of a well located in Gullfaks field by injecting CO2 through coiled tubing. The use of the CO2 injection method is due to the fact that it is a greenhouse gas, and its production in the atmosphere contributes to global warming. It is important to reduce its emission into the atmosphere and to boost the production of oil in the well. The CO2 is injected through the coil tubing to lighten the hydrostatic column and allow the fluid to move from the tubing to the surface. The completion and PVT data are processed in Pipesim and Prosper softwares. By integrating a number of calculations by using the nodal analysis methods and gas injection methods, the results obtained show that the well is not producing and by injecting sequestrated CO2 at the flow rate of 1.482 MMScft/d with an injection pressure of 2500 psig, the oil flow rate provided by the coiled tubing gas injection is 900 Stb/d. The profitability of the project is achieved over a period of 20 years with a net present value (NPV) of 11948858.5 and a return on investment after 5 years 2 weeks.